MBA, Faculty of Business Administration, Industrial University of Hochiminh City, Vietnam - Minh, Ngo Ngoc; Quang, Bui Van (International Journal of Psychosocial Rehabilitation, 2020)
The paper uses a two-step generalized method of moments (SGMM) to examine the impact of foreign direct investment (FDI) flows on social welfare in 13 Asian middle-income countries from 2000 to 2018. The empirical results show that the uneven distribution in the relationship between FDI and human development index (HDI) among countries. In particular, attracting high FDI inflows does not guarantee a positive impact on the country’s HDI. Furthermore, the study provides evidence of an inverse relationship between FDI and growth in social welfare, measured through the HDI. Additionally, FDI attraction, although having a negative impact on the education, income and health indexes in these Asian countries but the results are not statistically significant.